Plasma aldosterone concentrations elevation in hypertensive patients: the dual impact on hyperuricemia and gout - Song, Shuaiwei; Cai, Xintian; Hu, Junli; Zhu, Qing; Shen, Di; Ma, Huimin; Zhang, Yingying; Ma, Rui; Zhou, Pan; Yang, Wenbo; Hong, Jing; Zhang, Delian; et al. (Frontiers in Endocrinology, 2024)
Background: Prior research has highlighted the association between uric acid (UA) and the activation of the renin-angiotensin-aldosterone system (RAAS). However, the specific relationship between aldosterone, the RAAS's end product, and UA-related diseases remains poorly understood. This study aims to clarify the impact of aldosterone on the development and progression of hyperuricemia and gout in hypertensive patients.Methods: Our study involved 34534 hypertensive participants, assessing plasma aldosterone concentration (PAC)'s role in UA-related diseases, mainly hyperuricemia and gout. We applied multiple logistic regression to investigate the impact of PAC and used restricted cubic splines (RCS) for examining the dose-response relationship between PAC and these diseases. To gain deeper insights, we conducted threshold analyses, further clarifying the nature of this relationship. Finally, we undertook subgroup analyses to evaluate PAC's effects across diverse conditions and among different subgroups.Results: Multivariate logistic regression analysis revealed a significant correlation between the occurrence of hyperuricemia and gout and the elevation of PAC levels.Compared to the first quartile (Q1) group, groups Q2, Q3, and Q4 all exhibited a significantly increased risk of occurrence. Moreover, the conducted RCS analysis demonstrated a significant nonlinear dose-response relationship, especially when PAC was greater than 14 ng/dL, with a further increased risk of hyperuricemia and gout.Finally, comprehensive subgroup analyses consistently reinforced these findings.This study demonstrates a close association between elevated PAC levels and the development of UA-related diseases, namely hyperuricemia and gout, in hypertensive patients. Further prospective studies are warranted to confirm and validate this relationship.